Effectiveness and safety assessment of drospirenone/ethinyl estradiol tablet in treatment of PCOS patients: a single center, prospective, observational study - Li Li; Ruiqin Zhang; Jing Zeng; Hu Ke; Xiuhong Peng; Liying Huang; Hongmei Zhang; Zhijing Chen; Tian Tian Li; Qiuxiao Tan; Ying Yang; Xiaofang Li; et al. (BMC, 2020)
Abstract Background To investigate the effectiveness and safety of 3 mg drospirenone and 20 μg ethinyl estradiol tablet (3 mg DRSP/20 μg EE) in the treatment of polycystic ovary syndrome (PCOS). Methods This single center, prospective observational study was conducted in 140 patients with PCOS. They were prescribed 3 mg DRSP/20 μg EE in a 24/4/ regimen for 3 months. Patients were instructed to take oral DRSP/EE tablets (once daily) on the 2nd day of menstruation, for 28 consecutive days for 1 cycle. After 3 months of treatment, anthropometric assessments along with variations in sex hormones related index, glucolipid metabolic index, changes in bilateral ovarian volume, as well as adverse effect of the combination were evaluated. Results When compared to baseline, body mass index (BMI, 22.07 ± 4.09 vs. 21.35 ± 3.22, p < 0.001) and waist hip ratio (WHR, 0.86 ± 0.07 vs. 0.854 ± 0.06, p = 0.026) decreased significantly after treatment. Sex-hormones such as luteinizing hormone (LH) (10.88 vs. 5.81 U/L), testosterone (T) (1.85 vs. 1.51 nmol/L) and free androgen index (FAI) (5.37 vs. 1.50) decreased significantly after treatment (p < 0.001). Follicular stimulating hormone (FSH) increased significantly at 3 months as compared to before treatment (5.13 vs. 5.42 U/L, p = 0.009). Plasma insulin (11.03 vs. 11.10 pmol/L), fasting (4.97 vs. 4.93 mmol/L) and 2 h-blood glucose levels (7.18 vs. 7.04 mmol/L) did not change when compared to baseline. Plasma triglycerides (TG, 1.32 vs. 1.65 mmol/L) significantly increased 3 months after treatment when compared to before treatment (p < 0.001). However, high density lipoprotein-cholesterol (HDL-C) levels increased significantly after treatment (1.41 vs. 1.57 mmol/L, p < 0.001). It was seen that, when compared to baseline, bilateral ovarian volume (left and right) was significantly lower after treatment (p < 0.05). It was seen that 81 patients reported no adverse reactions. Of the common discomforts reported, breast swelling and pain, gastrointestinal disorder and dizziness and headache were most frequent. Conclusions Treatment of PCOS patients with3 mg DRSP/20 μg EE has shown beneficial hormonal and lipid profile along with considerable safety profile. Trial registration Chinese Clinical Trial Registry ChiCTR1900022001 , March 2019, retrospectively registered.